PENJADWALAN PRODUKSI MENGGUNAKAN METODE FCFS, CDS DAN GUPTA - Sugino, Wongso; Abdullah, Herlina (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Nowadays the scheduling system at PT Sutra Indah Utama performed manually and not using computing system. So the author would like to give suggestions that can be applied to production scheduling applications to determine overall production time or production time of each process. In this application, the company can see times comparison of production with the suggested method and the company method. PT Sutra Indah Utama is one of the companies that engaged in the manufacture of textile various types of fabrics with production systems pure Flowshop homage series. In the discussion here will discuss production scheduling from PT Sutra Indah Utama so it gets the maximum production scheduling. Therefore, the authors want to compare the time of company production with the suggested method. With CDS and Gupta proposed a method that may help to provide an alternative in production scheduling, which can accelerate the total production time or Makespan and maximizing the capacity of the machine optimally. Makespan is the total overall production time. CDS method faster than the Gupta method and the method the company, based on the results of the calculation of the average CDS method showed the result of the production time is short. Expected to be used and help to provide scheduling in PT Sutra Indah Utama .